2014
DOI: 10.1248/bpb.b13-00885
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the Risk of Upper Gastrointestinal Hemorrhage with Combination Therapy of Selective Serotonin Reuptake Inhibitors and Non-steroidal Anti-inflammatory Drugs

Abstract: It is thought that both selective serotonin reuptake inhibitors (SSRIs) and non-steroidal anti-inflammatory drugs (NSAIDs) can cause the adverse reaction of upper gastrointestinal hemorrhage (UGIH). To evaluate differences in the probability of UGIH occurring when SSRIs, NSAIDs, or both combined are administered, the authors performed a systematic review of related articles and a meta-analysis of data in those articles, which were identified by searching the literature published between 1999 and 2012 using Pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 19 publications
1
15
1
Order By: Relevance
“…We wanted to gather information regarding prescription drug use because our initial hypothesis was that SSRI use, due to its effect on platelet aggregation [12], could explain the difference between the sexes because they are prescribed more often to women. Also, there is evidence that SSRIs may be associated with upper gastrointestinal bleeding, especially when used concurrently with NSAIDs, APAs or OACs [33][34][35]. Although we found the expected association between SSRIs and women (crude OR, 2.8; 95%CI, 1.5-5.2), their use was not shown to be associated with FP results, even when there was concurrent use of these other drugs.…”
Section: Discussioncontrasting
confidence: 76%
“…We wanted to gather information regarding prescription drug use because our initial hypothesis was that SSRI use, due to its effect on platelet aggregation [12], could explain the difference between the sexes because they are prescribed more often to women. Also, there is evidence that SSRIs may be associated with upper gastrointestinal bleeding, especially when used concurrently with NSAIDs, APAs or OACs [33][34][35]. Although we found the expected association between SSRIs and women (crude OR, 2.8; 95%CI, 1.5-5.2), their use was not shown to be associated with FP results, even when there was concurrent use of these other drugs.…”
Section: Discussioncontrasting
confidence: 76%
“…Selective serotonin reuptake inhibitor intake has been associated with a modest increase in the risk of gastroduodenal bleeding (OR = 1.7, 95% CI = 1.4‐1.9) and the risk further increased for patients on joint NSAID therapy (OR = 4.02; 95% CI = 2.89‐5.15) . In our study population, H. pylori infection did not increase the risk of peptic ulcer bleeding in patients on selective serotonin reuptake inhibitor therapy.…”
Section: Discussionmentioning
confidence: 46%
“…While the role of steroids, antiplatelet drugs, and anticoagulants is long known, the synergistic effect of selective serotonin reuptake inhibitors (SSRIs) has until recently been overlooked. Over the past 15 years, several epidemiologic studies, summarized by three recent meta-analyses [226–228], have shown an association between SSRI use and the occurrence of UGIB, and found that this risk is further increased among patients, who concomitantly use NSAIDs [229, 230] and/or hold H. pylori infection [231], while it is lowered by concomitant PPI intake [227, 232]. The most plausible mechanisms underlying this detrimental effect include a marked decrease in serotonin platelet content, with consequent impairment of platelet aggregation in response to injury and prolongation of bleeding time as well as an increase in gastric acid secretion, with potential ulcerogenic activity [233, 234].…”
Section: Resultsmentioning
confidence: 99%
“…When given with NSAIDs, SSRIs may inhibit their metabolism, raising their blood levels and – through impairment of the hemostasis – may promote more severe bleeding. Since the concomitant use of both these drugs results in a significantly higher risk of UGIB than either drug alone [229, 230], this combination should be avoided whenever possible and, if unavoidable, adequate gastroprotection should be adopted from the very beginning [235]. …”
Section: Resultsmentioning
confidence: 99%